2021
DOI: 10.1111/1742-6723.13755
|View full text |Cite
|
Sign up to set email alerts
|

Use of intramuscular ketamine by paramedics in the management of severely agitated patients

Abstract: Objective Administration of a sedative agent is required for safe transport of prehospital patients with severe agitation to EDs. Ambulance services in Australasia use ketamine, droperidol or midazolam as first line agent but the optimal agent is uncertain. In Victoria, intramuscular (IM) ketamine is used. The present study aimed to examine the prehospital characteristics and ED outcomes of patients with severe agitation after IM ketamine administration. Methods A retrospective review was conducted for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…In a study on the effect of intramuscular ketamine as a sedative agent on severely agitated patients in the emergency department, the results were inconclusive as to its dose that may produce dissociation, which was already established as 3-4 mg/kg [ 14 ]. Intramuscular ketamine at a dose of <5 mg/kg provides adequate sedation with a low risk for intubation [ 15 ], but a dose of 4 mg/kg was effective in producing sedation for severe agitation but with an increased risk of intubation [ 16 ]. Reducing the dose to 2 mg/kg, O'Brien et al [ 17 ] reported that intramuscular ketamine caused adequate sedation and was effective for severe agitation without the need for intubation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the effect of intramuscular ketamine as a sedative agent on severely agitated patients in the emergency department, the results were inconclusive as to its dose that may produce dissociation, which was already established as 3-4 mg/kg [ 14 ]. Intramuscular ketamine at a dose of <5 mg/kg provides adequate sedation with a low risk for intubation [ 15 ], but a dose of 4 mg/kg was effective in producing sedation for severe agitation but with an increased risk of intubation [ 16 ]. Reducing the dose to 2 mg/kg, O'Brien et al [ 17 ] reported that intramuscular ketamine caused adequate sedation and was effective for severe agitation without the need for intubation.…”
Section: Discussionmentioning
confidence: 99%